Notes for an archaeology of Chilean dictatorship - Fuenzalida, Nicole (Revista Chilena de Antropología, 2017)
This article presents an historiography review of the main contributions made by Chilean archaeology in the study of the civic-military dictatorship (1973-1990). Its objective is to situate the status of the issue within the framework of the contemporary past and the archaeology of repression in Latin America to evaluate its possibilities and limitations. The bibliographic analysis shows limited but important efforts focused on two topics. One about forensic studies developed in the eighties and nineties, in relationship with legal process of crimes against humanity; and the other, centred on current reflection about detention, torture and extermination centres. To take distance from other theoretical lines, this archaeology combines a political choice for a useful praxis, with a critical point of view about traditional epistemology. An example is the study about the horror architecture that shows a promissory development in archaeology works during the Chilean dictatorship to discuss the past, which is very hard to talk for us, within a current context that combines politics, sites and collective memory, legal cases, the heritage rhetoric, among others.